KONTRIBUSI SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU DALAM PROSES BELAJAR MENGAJAR SERTA IMPLIKASINYA PADA HASIL BELAJAR DAN KARAKTER SISWA - Purwa Nugaraha, Andri; Gurat, T. (STKIP Subang, 2016)
Principals of good leadership should be able to work on improving the performance of teachers through staff capacity building program. Therefore, principals should have the competency-based supervision Permendiknas number 13 in 2007 that the principal has a duty to plan academic programs within the framework of professional supervision of teachers, carry out academic supervision of teachers by using approaches and techniques appropriate supervision and follow up the academic supervision of teachers in order to increase the professionalism of teachers. Professional teachers are needed in every school because with a professional teacher who will give birth to students who are competent, achievement, and has a culture and character of the nation so as to improve the quality of the school. In this paper, the researchers will try to examine the contribution of the principal supervision of teacher performance in teaching and learning and its implications on student learning outcomes